The Mediating Role of Dysfunctional Coping in the Relationship between Beliefs about the Disease and the Level of Depression in Patients with Rheumatoid Arthritis - Michal Ziarko; Ewa Mojs; Bartosz Piasecki; Wlodzimierz Samborski (The Scientific World Journal)
Aim. Rheumatoid arthritis is one of the most severe chronic diseases. In many cases it leads to disability and results in a decreased quality of life and increased levels of anxiety and depression. The problem that needs to be addressed is the following: which mental processes lead to increased levels of depression in patients with rheumatoid arthritis? Methods. 210 patients with rheumatoid arthritis hospitalized in rheumatology wards took part in the research. They filled in illness perception questionnaires (IPQ-R) and questionnaires for testing strategies of handling stress (Mini-COPE) and the level of depression (CES-D). Results. The observed correlation coefficients indicate that several elements of the perception of one’s disease moderately contribute to a high level of depression. Moreover, frequent use of dysfunctional coping strategies contributed to high levels of depression. Dysfunctional coping was moderately linked to depression. Conclusion. The conducted analyses confirmed the links between the beliefs about the disease and levels of depression and showed that the use of dysfunctional coping strategies mediates the relationship between the following elements of the representation of the disease: illness coherence, emotional representation, psychological attribution, risk factors, and the level of depression.